Materia medica of traditional knowledge: from east to west and beyond / Julenah Ag Nuddin - Julenah Ag Nuddin (Universiti Teknologi MARA Sabah, Kota Kinabalu, 2016)
Traditional knowledge is the accumulative knowledge that has been passed on since the beginning of time. It was recorded in various forms and formally in materia medica. Each ancient civilisations possessed its own materia medica; from east, Ancient China has Traditional Chinese Medicine, the Indians, their Ayurveda while the Greeks, Greek Medicine and several others. Both similarities and differences in materia medica are information which becomes valuable source in drug discovery. In combination with advanced and sophisticated tools, drug discovery programme aims to produce the wonder drugs for the betterment of humankind. However, in search of the magic bullet, we should not let haste and greed allow us to disregard materia medica as our heritage to be passed on.